Politik Media dalam Membingkai Perempuan (Analisis Framing Pemberitaan Kasus Video Porno Yahya Zaini dan Maria Eva di Harian Umum Kompas dan Suara Merdeka) - Mite Setiansah (FISIP Universitas Atma Jaya Yogyakarta, 2009)
Abstract: This research is a qualitative descriptive research which is aims to get an explanation about process of reality reconstruction doing by mass media, various kind of framing devices that is used, and woman representation at Kompas and Suara Merdeka news reporting about circulation of Yahya Zaini-Maria Eva porn video. In its execution, this research is using framing analysis method to gain information about way of mass media’s telling story. The data are collected by using qualitative content analysis applied to Kompas and Suara Merdeka news articles publish during December 2006. Unit of analysis determined based on Pan and Kosicki framing analysis model. Data validity is measured by triangulation technique. Data analysis is conducted by using the interactive data analysis technique. The result of this research shows that Kompas and Suara Merdeka have different point of view in reconstruction this case. Kompas showed careful news reporting while Suara Merdeka is more market oriented. Both of newspapers are uses same framing devices, including syntactic, script, thematic, and rhetoric. In representing woman, Kompas and Suara Merdeka are tending to frame woman in unfavorable ways.